2000
DOI: 10.1128/jvi.74.5.2430-2437.2000
|View full text |Cite
|
Sign up to set email alerts
|

The In Vitro-Synthesized RNA from a cDNA Clone of Hepatitis E Virus Is Infectious

Abstract: Hepatitis E virus (HEV) is an important etiological agent of epidemic and sporadic hepatitis, which is endemic to the Indian subcontinent and prevalent in most of the developing parts of the world. The infection is often associated with acute liver failure and high mortality, particularly in pregnant women. In order to develop methods of intervention, it is essential to understand the biology of the virus. This is particularly important as no reliable in vitro culture system is available. We have constructed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
118
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(127 citation statements)
references
References 37 publications
9
118
0
Order By: Relevance
“…These data, taken in conjunction with the demonstration that capped Sar-55 transcripts infected chimpanzees, whereas uncapped transcripts did not, suggested that a cap is required for viral viability. The in vivo transfection results provide an explanation for the failure of Panda et al (19) to infect rhesus monkeys with HEV transcripts from an Indian strain, because they used only uncapped transcripts. However, it is not clear how they were able to infect cultured Hep G2 cells with uncapped transcripts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These data, taken in conjunction with the demonstration that capped Sar-55 transcripts infected chimpanzees, whereas uncapped transcripts did not, suggested that a cap is required for viral viability. The in vivo transfection results provide an explanation for the failure of Panda et al (19) to infect rhesus monkeys with HEV transcripts from an Indian strain, because they used only uncapped transcripts. However, it is not clear how they were able to infect cultured Hep G2 cells with uncapped transcripts.…”
Section: Discussionmentioning
confidence: 93%
“…Recently it was reported that transfection of cultured Hep G2 cells with noncapped RNA transcripts from a full-length cDNA clone of an Indian strain of HEV resulted in productive replication (19). However, RNA transcripts from the cDNA clone were not infectious for rhesus monkeys when inoculated intrahepatically, as has been done successfully for other positivesense RNA viruses.…”
Section: H Epatitis E Virus (Hev) Is An Unclassified Nonenvelopedmentioning
confidence: 99%
“…7,8 Further understanding of the HEV replication came from the development of infectious cDNA clone of HEV which helped in elucidating the importance of 5 0 end cap, RdRp activity and nonstructural polyprotein processing. 9,10 Mutational and strand-specific PCR analysis using the HEV replicon helped in delineating the bi-cistronic sub-genomic RNA based expression strategy for ORF2 and ORF3 proteins and the presence of an additional untranslated region (UTR) in the intergenic region with probable cis reactive element thought to function as sub-genomic promoter. [11][12][13][14] Till date only one cis-acting element has been characterized, that in the 3 0 UTR, which was shown to form stable secondary structures and help in the localization of RdRp.…”
Section: Thementioning
confidence: 99%
“…28 ORF1 polyprotein processing has been observed in transfection studies of infectious HEV cDNA clone. 9 The exact cleavage sites of the ORF1 polyprotein are still not known. Another study demonstrating partial cleavage of the full-length 185 kDa ORF1 polyprotein had been shown.…”
mentioning
confidence: 99%
“…The Korean avian HEV belongs to genotype 1. The construction of infectious cDNA clones of HEV provided useful tools to elucidate the structural and functional relationship of HEV genes and facilitate the study of HEV pathogenesis in animal models (Huang et al, 2005a;Okamoto, 2011;Panda et al, 2000;Yamada et al, 2009b). Thus far, only the genotype 2 avian HEV infectious clone is available (Huang et al, 2005b;Kwon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%